Students' Analytical Thinking Skills through Tutorial Video Assisted Inquiry Approach on Direct Current Electricity Grade XII Senior High School - Vira Septi Amelia; Susilawati Susilawati; Joko Budi Poernomo (Berkala Ilmiah Pendidikan Fisika, 2022)
Students' analytical thinking skills are still lacking, causing students' understanding of physics lessons to be less than optimal. The research was conducted to examine the effectiveness of direct current electric video with an inquiry approach to students' analytical thinking skills and student responses to the video. The research method applied in this research is quasi-experimental with the research design of Nonequivalent Control Group Design. The sampling technique is purposive sampling data collection techniques using analytical thinking skills tests and questionnaires to video tutorials responses. The data analysis technique uses parametric quantitative analysis. The results of the analysis of hypothesis testing on the data of analytical thinking skills that had been carried out showed that the video tutorial learning media has not been effective in improving students' analytical thinking skills, while the results of student responses to direct current electric video tutorial learning media obtained a percentage of 70.67% and classified as good category. Students' analytical skills require more intensive practice and challenging routine assignments. Students' interest in the tutorials provided can only increase motivation to be involved in learning. The implications of this research can focus on innovative video tutorials on contextual physics experiments in life and more challenging experiments.